The Role of Independent Learning Independent Campus (MKBM) in Building Human Resources Character with Insight into Sustainable Development Goals (SDGs) - Febriatmoko, Bogy; Wartini, Sri; Hasibuan, P Erianto; Prananta, Widya; Soliha, Euis (Universitas Airlangga, 2025)
This study aims to analyze the influence of the Sustainable Development Goals (SDGs) and the Independent Learning-Independent Campus (MBKM) policy on the formation of human resource (HR) character, as well as examine the role of MBKM policy moderation in the relationship between the SDGs and the character of human resources. This study was conducted at Semarang State University (UNNES) using a quantitative approach through Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. The results of the study show that the SDGs have a positive and significant influence on the formation of human resource character. The MBKM policy also plays an important role in significantly strengthening the character of human resources. In addition, the MBKM policy has proven to be able to moderate the relationship between the SDGs and the character of human resources, thus strengthening the relationship between the two. The addition of the MBKM policy moderation variable improves the model's ability to explain the variability of human resource characters, which shows the significant contribution of this policy in supporting the achievement of the SDGs. These findings underscore the importance of implementing the MBKM policy in supporting the achievement of the SDGs, especially in the context of higher education to form human resources with superior character and able to face global challenges.